MENGURANGI KEBIASAAN MEROKOK MENGGUNAKAN PENDEKATAN KONSELING BEHAVIORAL STRATEGI SELF-CONTROL PADA SISWA SMA NEGERI 1 NATAR TAHUN AJARAN 2012/2013 - Dika Ananda; Giyono Giyono; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this research to find the reduction of smoking habitual by using approach of counseling behavioral strategy self-control of the students at SMAN 1 Natar year of 2012/2013.The research design is one-group pretest-posttest design. Problem of this research is there are smoking habitual students. There are 6 students whohavesmoking habitualas thesubjects of this research.The  data collectingtechniquesusedparticipant observationandinterviews.Result of this research showed that the smoking habitual can reduce by using approach of counselingbehavioral strategy self-control, it can be seen fromthe results ofdata analysis by using theWilcoxontest, the results of pretestandposttestshows that significancy test 5% p= 0,026 ; p0,05,  it can be concluded that Hois rejectedandHa is accepted, it means thatsmoking habitual can reduce by using approach of counselingbehavioral strategy self-control.The conclusionsof this researchis smoking habitual can reduce by using approach of counselingbehavioral strategy self-control of the students SMAN 1 Natar year of 2012/2013 . The suggestions are (1) the students that have smoking habitual should have can reduce to smoking habitual, therefore in their daily activity will not get any abstacle to make an interaction to others. (2) teacher of Guidance and Counselling (BK) should apply approach of counseling behavioral strategy self-control to minimize smoking habitual. (3) for another researcher should take the same research with different ages. Keyword : Smoking habitual, Approach of counselingbehavioral strategy self-control